2017
DOI: 10.1152/japplphysiol.00256.2017
|View full text |Cite
|
Sign up to set email alerts
|

Lower body negative pressure reduces optic nerve sheath diameter during head-down tilt

Abstract: The microgravity ocular syndrome (MOS) results in significant structural and functional ophthalmic changes during 6-mo spaceflight missions consistent with an increase in cerebrospinal fluid (CSF) pressure compared with the preflight upright position. A ground-based study was performed to assess two of the major hypothesized contributors to MOS, headward fluid shifting and increased ambient CO, on intracranial and periorbital CSF. In addition, lower body negative pressure (LBNP) was assessed as a countermeasur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…Likewise terrestrial head down studies with and without hypercapnia have demonstrated increased retinal nerve fiber layer on OCT and might still prove to be a suitable terrestrial analog to test hypotheses and potential countermeasures to SANS. [73][74][75][76][77][78][79][80][81][82] These countermeasures include metabolic and pharmacologic treatments 69,[83][84][85][86][87] in the one carbon pathways; 63,69 lower body negative pressure; [74][75][76] and swim goggles to affect the translaminar pressure gradient. While current data does not seem to support prolonged, significant elevations of ICP to the levels seen in IIH, throughout LDSF, Lawley et al proposed that even mild elevations of ICP for a prolonged duration may contribute to the structural changes seen in SANS.…”
Section: Oct and Sansmentioning
confidence: 99%
“…Likewise terrestrial head down studies with and without hypercapnia have demonstrated increased retinal nerve fiber layer on OCT and might still prove to be a suitable terrestrial analog to test hypotheses and potential countermeasures to SANS. [73][74][75][76][77][78][79][80][81][82] These countermeasures include metabolic and pharmacologic treatments 69,[83][84][85][86][87] in the one carbon pathways; 63,69 lower body negative pressure; [74][75][76] and swim goggles to affect the translaminar pressure gradient. While current data does not seem to support prolonged, significant elevations of ICP to the levels seen in IIH, throughout LDSF, Lawley et al proposed that even mild elevations of ICP for a prolonged duration may contribute to the structural changes seen in SANS.…”
Section: Oct and Sansmentioning
confidence: 99%
“…Studies investigating SANS with a spaceflight analog, head-down tilt, have reported ONS distension likely due to elevated ICP in the head-down tilt position 31 . In the present study, we did not observe an increase in ONS cross-sectional area after spaceflight in most individuals, which may indicate ICP is not pathologically elevated in space.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Killer et al showed a potential for increased intraocular pressure caused by SAT fibers and by extension this could potentially affect astronauts with space flight associated neuroocular syndrome [17]. Taken together, available data implicates the PAC and SAT in CNS pathologies.…”
Section: Introductionmentioning
confidence: 91%